Peranan Patroli Satuan Sabhara Dalam Upaya Pengoperasian Tindak Kejahatan Di Wilayah Hukum Polda Bali - I Nyoman Loka Hari Prabawa; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
The carrying out of routine police operations is capable of preventing crime and harmonizing public obedience. This study aims to explain the patrol capabilities of the Sabhara Unit in an effort to operate criminal acts in the jurisdiction of the Bali Regional Police and explain what factors are hindering the Sabhara Unit patrols in the effort to operate criminal acts within the jurisdiction of the Bali Regional Police. The type of research used is empirical legal research. The approach used is the Legislative Regulations approach. Data sources are primary and secondary legal data sources. Data collection techniques were carried out by interviewing rules and documentation. After the legal materials are collected, they are processed and analyzed using qualitative method analysis. The results showed that the Sabhara Unit patrol capability in an effort to operate a crime in the jurisdiction of the Bali Regional Police was to arrest and report the criminal executor who was caught red-handed while patrolling, securing the victim, executor, witnesses, evidence, and the location of the next case the factors that hinder patrols of the Sabhara Unit in an effort to operate criminal acts in the jurisdiction of the Bali Regional Police, namely internal factors, namely lack police personnel, information, no evidence found and lack of infrastructure, while external factors are lack of public awareness, victims do not immediately report and fear the Police.